2018
DOI: 10.5812/iranjradiol.60955
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Radiation Dose and Cancer Risk Estimation in Common Diagnostic Radiology Procedures

Abstract: Background: Diagnostic radiology by the use of ionizing radiation plays a main contribution in the collective dose of human population. Knowing the radiation dose received by patients during a radiological examination is essential to prevent the excess health risk of exposure. Objectives: The aim of this study was to estimate the collective dose and calculate the cancer risk probability due to common radiological procedures in four radiology imaging centers of Iran. Patients and Methods: Four hundred seventy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
7
2
Order By: Relevance
“…In addition, when the pelvis is examined likewise, the total radiation dose can be increased (e.g., up to 15.5 mGy based on the data in Tables 2 and 3). These values are higher than accepted values from other studies in routine conditions [19][20][21][22][23][24][25][26][27] (Table 4). Also, Metaxas et al, 23 Although patient dose is less in plain radiography compared to other X-ray procedures, severely injured trauma patients may be exposed to several radiation fields leading to higher doses to the pelvis (see Table 3).…”
Section: Discussioncontrasting
confidence: 78%
“…In addition, when the pelvis is examined likewise, the total radiation dose can be increased (e.g., up to 15.5 mGy based on the data in Tables 2 and 3). These values are higher than accepted values from other studies in routine conditions [19][20][21][22][23][24][25][26][27] (Table 4). Also, Metaxas et al, 23 Although patient dose is less in plain radiography compared to other X-ray procedures, severely injured trauma patients may be exposed to several radiation fields leading to higher doses to the pelvis (see Table 3).…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast, CALDose-X software estimates the effective dose closer to the actual values (33) . It seems that one of the reasons for the high effective dose in this study compared to other ones was the difference between the dose calculation software and how to calculate the method with other studies (27,30,34,35) .…”
Section: Discussionmentioning
confidence: 74%
“…This confirms the need to continue such studies and to extend them to other X-ray diagnostic methods. Mashhad (36) 0.34 1.78 Kashan (37) 0.37 1.39 ChaharmahalBakhtiari (38) 0.7 6.92 Iran (39) 0.41 2.83 Esfahan (40) 0.74 6.84 Hamedan (34) 0.43 2.15 Mean ESD (in other studies in Iran) 0.49…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…TLDs that have minimum fading, high sensitivity, and high thermoluminescence are used exclusively for external dosimetry of the patient. More ever, due to their small size and proper structure, they do not cause any harm to the patient [21,22]. Assessment of The TLD tablets placed on the patient's body indicated that the absorbed radiation dose of patients is 7.72 ± 4.73 mSv.…”
Section: Absorbed Doses Measurementmentioning
confidence: 99%